1992
DOI: 10.5144/0256-4947.1992.235
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Newborn Screening Program: ARAMCO Experience, The National Need and Recommendations

Abstract: Comprehensive screening programs for congenital diseases of newborn infants are lacking at a national or regional level. A comprehensive newborn screening program modified to the needs and resources available was established in ARAMCO Dhahran Health Center. This program includes screening for congenital hypothyroidism, phenylketonuria, abnormal hemoglobins, glucose-6-phosphate dehydrogenase deficiency, and blood group incompatibilities. Several problems were encountered during the operation which required seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1

Year Published

1992
1992
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 14 publications
2
11
1
Order By: Relevance
“…We found the incidence of confirmed infants with CH in our series, 1:3417, to be comparable to what has been reported by Abu-Osba et al 4 from the Eastern Province of Saudi Arabia and consistent with other reports from Europe and North America. 1,[10][11][12][13][14] However, if we consider infants with positive cord screening in whom confirmation was not possible, the incidence will be even higher at 1:2836.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…We found the incidence of confirmed infants with CH in our series, 1:3417, to be comparable to what has been reported by Abu-Osba et al 4 from the Eastern Province of Saudi Arabia and consistent with other reports from Europe and North America. 1,[10][11][12][13][14] However, if we consider infants with positive cord screening in whom confirmation was not possible, the incidence will be even higher at 1:2836.…”
Section: Discussionsupporting
confidence: 81%
“…6,[10][11][12][13][14][15] Furthermore, our experience has since shown that the successful implementation of any screening program depends not only on the efficient and comprehensive collection of specimens, transport and laboratory processing but also on access to patients to ensure prompt recall for further testing and therapy. 1,4,6 Variable degrees of enthusiasm among medical teams, difficulties in locating suspicious cases with occasional lack of addresses and telephone numbers, and poor compliance from parents are among the difficulties. Adequate health awareness and education of parents are important for cooperation in recall, compliance and subsequent life-long therapy and follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Studies conducted in some parts of the Middle East suggest that the incidences of inborn errors of metabolism are higher here than anywhere else in the world, due to the more common occurrence of consanguineous marriages. [2][3][4] Over the last two decades, liquid chromatography tandem mass spectrometry (LC-MS/MS) has become the predominant technique for analyzing dried blood spots on Guthrie filter cards, to screen for inborn errors of metabolism, including amino acid, fatty acid, and organic acid disorders. 5,6 These biomarkers in the blood spot are susceptible to environmental conditions, such as heat and humidity.…”
Section: Introductionmentioning
confidence: 99%
“…
In the first article of this issue Abu-Osba et al [1] describe their experience in the establishment and implementation of a neonatal screening program which has now been running for more than a decade at the Arabian American Oil Company (ARAMCO). The conditions included were hypothyroidism and phenylketonuria (PKU) which are commonly screened for in other countries and also abnormal hemoglobins, glucose-6-phosphate dehydrogenase (G-6-PD) deficiency and blood group incompatibility which were of particular interest to the study population.

The principle of neonatal screening is a universally accepted dogma in the philosophy of modern health care planning which emphasizes prevention as being more important than cure.

…”
mentioning
confidence: 99%